Pengaruh Investasi Energi Terbarukan, Ekoefisiensi dan Pengungkapan Emisi Karbon terhadap Nilai Perusahaan - Khalisa Zahra Putri; Muhammad Asril Khairi; Christina Dwi Astuti (CV. Ulil Albab Corp, 2026)
This study aims to analyze the effect of renewable energy investment, eco-efficiency, and carbon emission disclosure on firm value in energy and basic materials companies listed on the Indonesia Stock Exchange for the 2021–2025 period, specifically companies engaged in mining, nickel, and/or gold. The study employed a quantitative approach with secondary data obtained from annual reports, sustainability reports, and official sources from the companies and the Indonesia Stock Exchange. The sample was selected using a purposive sampling technique. Of the 220 observations that met the initial criteria, 73 outliers were eliminated, resulting in 147 observations used in the analysis. The analytical method used was multiple linear regression with IBM SPSS Statistics. The results showed that renewable energy investment had no significant effect on firm value. Conversely, eco-efficiency had a positive and significant effect on firm value, indicating that better eco-efficiency implementation led to higher firm value. Furthermore, carbon emission disclosure also had a positive and significant effect on firm value, indicating that corporate transparency in disclosing carbon emission information can increase investor confidence and market valuation of the company. These findings indicate that sustainability aspects, particularly eco-efficiency and carbon emissions disclosure, play a significant role in increasing corporate value.